The Influence of Interval Training And Circuit Training on The Physical Fitness of Taekwondo Athletes in The Age Group Of 9-13 Years - Al Badra, Dhani Dharweisy Al Badra; Abdulaziz, Moch. Fahmi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to determine and compare the effects of interval training and circuit training on the physical fitness improvement of Taekwondo athletes aged 9 to 13 years in Batang Regency. The research employed a quasi-experimental method with a pretest-posttest group design. Subjects were divided into two treatment groups, each undergoing a structured training program consisting of 12 sessions over a period of 4 weeks. The training focused on enhancing physical fitness, measured using the bleep test which covers endurance, strength, agility, and aerobic capacity. The results showed that the interval training group experienced an average improvement of approximately 31.1%, while the circuit training group showed a higher increase of around 35.5%. The paired sample t-test indicated a significant difference between the pretest and posttest results in both groups (t count > t table). However, the circuit training group demonstrated slightly higher t values and percentage gains than the interval group, suggesting that while both methods are effective, circuit training may offer a more optimal approach to improving physical fitness in young athletes. This research is expected to serve as a valuable reference for coaches and trainers in selecting appropriate training methods, and to help athletes better understand the importance of structured physical fitness development.